Resonansi Mistisisme Sufi dalam Sastra Nusantara: Konsep Wahdat al-Wujūd dalam Lagu “Satu” - Iklila, Difla (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2025)
Abstract: This paper examines the concept of Wahdat al-wujūd as expressed in Ahmad Dhani's song